Populism: Root Causes, Power Grabbing and Counter Strategy - Karl Aiginger (Intereconomics, 2020)
The economic agenda of bringing jobs back and improving dynamics can sometimes work in the short run, if past fiscal prudence has left some space for higher government expenditures for low incomes. However, in the long run, protection and redistribution without active components, innovation and new firms do not work.
Keywords: 330